The Laffer curve for high incomes - Jacob Lundberg (Luxembourg Income Study (LIS), 2017)
An expression for the Laffer curve for high incomes is derived, assuming a constant Pareto parameter and elasticity of taxable income. The peak of this Laffer curve is given by the well-known Saez (2001) expression. Microsimulations using Swedish population data show that the simulated curve matches the theoretically derived Laffer curve well, suggesting that the analytical expression is not too much of a simplification. Policy conclusions do not change much when income effects are taken into account. A country-level dataset of top effective marginal tax rates and Pareto parameters is assembled. This is used to draw Laffer curves for 27 OECD countries. Revenue-maximizing tax rates and degrees of self-financing for a small tax cut are also computed. The results indicate that degrees of self-financing range between 28 and 195 percent. Five countries have higher tax rates than the peak of the Laffer curve.
Keywords: 330